2021
DOI: 10.21037/tau-20-1378
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-145 is associated with perineural invasion in penile carcinoma

Abstract: Background: Human papillomavirus (HPV) infection is a risk factor for penile cancer (PC). The miR-145 expression has been correlated to this virus genomic amplification. In this context, this work aims to determine the expression level of miR-145 in penile tumors infected by high-risk HPV and correlate it with the clinicopathological characteristics of the tumor and protein expression of p53.Methods: Formalin-fixed paraffin-embedded from 52 patients with PC, at diagnosis and prior to any cancer treatment, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To our knowledge, to date, only 11 studies have investigated the differential expression of microRNAs (miRNAs) in this disease [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. miRNAs are a class of small non-coding RNAs (ncRNAs) that regulate gene expression post-transcriptionally by repressing translation and/or initiating mRNA degradation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, to date, only 11 studies have investigated the differential expression of microRNAs (miRNAs) in this disease [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. miRNAs are a class of small non-coding RNAs (ncRNAs) that regulate gene expression post-transcriptionally by repressing translation and/or initiating mRNA degradation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, our group also observed that miR-145-5p is a potential biomarker for perineural invasion ( 13 ), an indicator of worse survival in patients with penile cancer ( 55 ). MiR-145-5p also has therapeutic potential since the use of mimics of this microRNA in cervical cancer can inhibit cell proliferation ( 56 ) and metastasis in ovarian cancer ( 57 ).…”
Section: Introductionmentioning
confidence: 77%
“…Thus, biological markers that can predict or assist in diagnosing this phenomenon are of great clinical importance. Some markers based on ncRNAs have been investigated, especially those associated with lymph node metastasis ( 11 , 12 ), perineural invasion ( 13 ), and HPV ( 14 ).…”
Section: Introductionmentioning
confidence: 99%